A linguagem do ‘amor colonial’. O discurso do poder pastoral na justificação da escravidão - Siqueira, Carlos Henrique R. (Sankofa (São Paulo), 2008)
In this article I follow the itinerary of discourses which provided the conditions to ideological reproduction of atlantic slavery in the 16th Century. Through the analysis of the Gomes Eannes Zurara’s heroic narrative, the Crônica dos feitos de Guiné, I discuss the some arguments employed by the author to adapt to the christian and modern world a practice which, dispite the fact that was narrated as a continuation of an old roman institution, needed be jusified to be legitimated in its new spacial and economic configuration.